Risk Factor of Falling in Individual with Type 2 Diabetes Mellitus - Sari, Dwi Rosella Komala; Pristianto, Arif (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background: Diabetes Mellitus (DM) is characterized by hyperglycemia. Type 2 diabetes mellitus (T2DM) is a common type of DM. It gives microvascular and macrovascular complications in the body. The diabetic peripheral neuropathy (DPN) is declared as the highest complication of T2DM, about two third cases of DM. It impacts to high risk of falling. As well the duration of DM and body balance also contributed to balance stability. Poor of those factors increase the risk of falling. However, previous studies have not declared the dominant factor contributing to falling in individuals with T2DM. Purpose: The purpose of this study was to determine the dominant factors contributing in the risk factors of falling risk in individuals with T2DM. Methods: The patients confirmed T2DM by medical diagnosis and had 5 years above of T2DM. The glycemic level was set by taken blood sample from intravenous after fasted for 8 hours. The Michigan Neuropathy Screening Instrument (MNSI) was used to screen the DPN. The static balance was measured by the Berg Balance Scale (BBS), while dynamic balance was measured by Time Up and Go test. The risk of falling was confirmed by the cut score of the Timed Up and Go test. This study has done in DM community, Surakarta, Central Java, Indonesia. Results: The correlation test showed the duration of DM and DPN had correlation with balance. had a contribution to the risk of falling significantly (p-value <0.05). The Logistic Regression Model presented the duration of DM (OR : 1.008, p-value=0.001, 95% CI = 1.518 – 4.943) dan balance (OR = 0.317, p-value = 0.001, 955 CI = 1.518 – 4.943) influenced the risk of falling in individuals with T2DM. Conclusion: The longer suffer of DM and uncontrol glycemic level induced the development of DPN. The duration of suffering from DM must be accompanied by good lifestyle management to avoid development some complications of DM.